Advances in genetics. - Hall, Jeffrey C.; Dunlap, Jay C.; Friedmann, Theodore, 1935- (Advances in genetics ;, 2003)
The field of genetics is rapidly evolving and new medical breakthroughs are occurring as a result of advances in knowledge of genetics. This series continually publishes important reviews of the broadest interest to geneticists and their colleagues in affiliated disciplines. The field of genetics is rapidly evolving and new medical breakthroughs are occurring as a result of advances in knowledge of genetics. This series continually publishes important reviews of the broadest interest to geneticists and their colleagues in affiliated disciplines.